Implications for liquidity from innovation and transparency in the European corporate bond market - Marco Laganá; Martin Perina; Isabel von Köppen-Mertes; Avinash Persaud (European Central Bank (ECB), 2006)
This paper offers a new framework for the assessment of financial market liquidity and identifies two types: search liquidity and systemic liquidity. Search liquidity, i.e. liquidity in “normal” times, is driven by search costs required for a trader to find a willing buyer for an asset he/she is trying to sell or vice versa. Search liquidity is asset specific. Systemic liquidity, i.e. liquidity in “stressed” times, is driven by the homogeneity of investors - the degree to which one's decision to sell is related to the decision to sell made by other market players at the same time. Systemic liquidity is specific to market participants' behaviour. This framework proves fairly powerful in identifying the role of credit derivatives and transparency for liquidity of corporate bond markets. We have applied it to the illiquid segments of the European credit market and found that credit derivatives are likely to improve search liquidity as well as systemic liquidity. However, it is possible that in their popular use today, credit derivatives reinforce a concentration of positions that can worsen systemic liquidity. We also found that post-trade transparency has surprisingly little bearing on liquidity in that where it improves liquidity it is merely acting as a proxy for pre-trade transparency or transparency of holdings. We conclude that if liquidity is the objective, pre-trade transparency, as well as some delayed transparency on net exposures and concentrations, is likely to be more supportive of both search and systemic liquidity than post-trade transparency.
Keywords: G14; G15; G18; 330; Financial market functioning; liquidity; transparency; credit markets and financial innovation.; Bankenliquidität; Mindestreserve; Geldpolitik; Finanzmarkt; Finanzprodukt; EU-Staaten